TEKNOLOGI PENGELASAN SEBAGAI MODERASI REGULASI PEMERINTAH DAN KARAKTERISTIK PEKERJA TERHADAP DAYA SAING TENAGA KERJA - Affandy Agusman Aris (AkMen JURNAL ILMIAH, 2017)
a qualitative explanative assosiative research was conducted with the aim of knowing the moderation effect of welding technology on the influence of government regulation and worker characteristics on labor competitiveness. Research conducted at PT. Indonesian Ship Industry (IKI) Makassar, Training Center (BLK) Makassar, PT. Vale Indonesia Luwu Timur, PT. Eastern Pearl Flour Mills Makassar, Center for Material and Technical Products (B4T) Bandung, PT. Dirgantara Indonesia Bandung, PT. Garuda Maintenace Facility (GMF) Cengkareng Tangerang, National Agency for Professional Certification (BNSP) Jakarta, Ministry of Manpower in Jakarta, Ministry of Industry in Jakarta, Profession Certification Institute (LSP) LAS Jakarta, PT. Pindad Bandung, and Indonesian Welding Association (IWA). As the study population. The sampling technique used in this research is non-probability sampling that is purposive sampling is the method of determining the sample based on certain criteria and the research sample is 90 respondents. The research approach used is quantitative with the analysis tool is Generalized Structure Component Analysis (GSCA) . Obtained by analysis result which states that there is influence of variable of Government Regulation and worker characteristic and welding technology to Competitiveness of Labor. It was also found that Welding Technology modifies the influence of Government Regulatory variables and quasi moderator and strengthening worker characteristics.